The Accuracy of Preoperative Imaging in The Detection of Gallbladder Carcinoma - Younis , Saeed Nadhim (Diyala Journal of Medicine, 2019)
Introduction: Primary carcinoma of the gallbladder is an uncommon, aggressive malignancy that affects women more frequently than men. Older age groups are most often affected, and coexisting gallstones are present in the vast majority of cases. The symptoms at presentation are vague and are most often related to adjacent organ invasion, and the radiologic findings in early-stage cancers are subtle and may mimic those of acute or chronic cholecystitis and many gallbladder carcinomas are diagnosed in an advanced stage ,therefore, despite advances in cross-sectional imaging, early-stage tumors are not often encountered. Objectives: To determine the utility of ultrasound and multidetector CT imaging in the surgical management of gallbladder carcinoma. It provides a road map for surgical procedures to be taken. Materials and Methods: The data from 40 patients with histologically proven adeno carcinoma of gallbladder from the period of March 2006 to December 2010 analyzed, in a prospective study done in Rizgari teaching Hospital and Soran Diagnostic center Results: Preoperative detection rate of both ultrasound and CT scan was 60% and the diagnostic accordance rate before and after operation was low in early stages T 1 & 2 (23.5%) versus (86.9%) in advanced stages T 3 & 4. The female to male ratio was 4:1. The gallstone was closely related to gallbladder carcinoma and was seen in 90% of cases. Conclusion: proper utilization of different imaging modalities is essential for early detection and treatment options of gallbladder carcinoma by using comprehensive imaging techniques like dual Phase multidetector CT coupled with 3D volume rendered reconstruction.